2020
DOI: 10.1186/s11689-020-09333-2
|View full text |Cite
|
Sign up to set email alerts
|

Affective and psychotic reactivity to daily-life stress in adults with 22q11DS: a study using the experience sampling method

Abstract: Background 22q11.2 deletion syndrome (22q11DS) is a genetic disorder associated with an increased risk of psychiatric disorders. Vulnerability for psychopathology has been related to an increased reactivity to stress. Here, we examined affective states, perceived stress, affective and psychotic reactivity to various sources of environmental stress using the experience sampling method (ESM), a structured diary technique allowing repeated assessments in the context of daily life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 44 publications
(60 reference statements)
8
26
3
Order By: Relevance
“…As predicted, participants with 22q11DS reported more intense momentary psychotic experiences than HC. This is consistent with a recent EMA study from Schneider et al (2020) conducted on an independent sample of adults with 22q11DS that also observed more intense psychotic experiences than HC in their daily-life. Interestingly, participants with 22q11DS also reported more frequent psychotic experiences throughout the assessment period, an indicator that was not measured in Schneider et al (2020).…”
Section: Psychotic Experiences In Daily-lifesupporting
confidence: 92%
See 2 more Smart Citations
“…As predicted, participants with 22q11DS reported more intense momentary psychotic experiences than HC. This is consistent with a recent EMA study from Schneider et al (2020) conducted on an independent sample of adults with 22q11DS that also observed more intense psychotic experiences than HC in their daily-life. Interestingly, participants with 22q11DS also reported more frequent psychotic experiences throughout the assessment period, an indicator that was not measured in Schneider et al (2020).…”
Section: Psychotic Experiences In Daily-lifesupporting
confidence: 92%
“…This is consistent with a recent EMA study from Schneider et al (2020) conducted on an independent sample of adults with 22q11DS that also observed more intense psychotic experiences than HC in their daily-life. Interestingly, participants with 22q11DS also reported more frequent psychotic experiences throughout the assessment period, an indicator that was not measured in Schneider et al (2020). Of note, the population of Schneider et al (2020) study was older (mean age HC = 39.91 and 22q11DS = 34.11) than the one of the present study, but reported a similar mean intensity of psychotic experiences, which argues for an emergence of psychotic experiences relatively early during development.…”
Section: Psychotic Experiences In Daily-lifesupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, Wilson and al. (35) validated EMA feasibility in a population with moderate intellectual disability but this technique had rarely been used in 22q11DS population (39,40). This is why we took time to go through the protocol with each participant and to carefully read and explain each item, as well as closely monitoring them during the full EMA period.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Of note, this method was found reliable to assess vulnerable populations, such as individuals with intellectual disability (35) or schizophrenia (36-38). To the best of our knowledge, this technique has only been used twice in adults with 22q11DS to characterize affective and psychotic reactivity to dailylife stress (39,40). In individuals with ASD, there is a paucity of studies (41)(42)(43)(44)(45)(46)(47)(48)(49), most of them focusing on the feasibility of the EMA technique.…”
Section: Introductionmentioning
confidence: 99%